Otitis Externa in Secondary Care: A Change in Our Practice Following a Full Cycle Audit - Liu, Zhaobo; Slim, Mohd Afiq Mohd; Scally, Catherine (International Archives of Otorhinolaryngology, 2018)
Introduction Patients presenting with otitis externa are a common thing in otolaryngology units. However, the practice has not been standardized due to a lack of consensus over the management of this condition in secondary care. The National Institute for Health and Care Excellence (NICE) guideline has been published targeting the general practitioners, but it may be relevant in cases of hospital first-time attenders.Objective To conduct an audit of the investigative and prescription practice for hospital first-time attenders in our department against the NICE guideline for otitis externa.Methods The case notes of the patients presenting with otitis externa were reviewed. The data collation included the performance of ear swabs and choice of eardrops.Results An initial audit showed that ear swabs were sent in 14 out of 19 cases, of which 11 grew either Pseudomonas aeruginosa or Staphylococcus aureus (organisms that are sensitive to empirical treatment). A re-audit showed higher adherence to NICE recommendations, with ear swabs sent in only 3 out of 25 cases. The initial audit also demonstrated Sofradex (Sanofi-Aventis, Paris, France) as the most popular empirical eardrop. Following our recommendation, the re-audit showed that Betnesol-N (GSK, Brentford, UK) was administered in 24 out of 25 cases.Conclusion We recommend Betnesol-N due to its cost-effectiveness. Ear swabs should be reserved for refractory cases only. Posters and email reminders are effective means of disseminating information within the hospital.
Keywords: otitis externa; microbiology; epidemiology